Women's experiences of sexual health after first‐time myocardial infarction. Issue 23 (11th October 2013) - Søderberg, Lene H; Johansen, Pernille P; Herning, Margrethe; Berg, Selina K
Abstract : Aims and objectives: To investigate women's experience of sexual problems after a myocardial infarction. Background: Sexual problems among female patients with ischaemic heart disease have received little study but have been found to be highly prevalent in the research. Sexual problems have been found to influence quality of life and well‐being, and sexual dysfunction has been associated with anxiety and depression. International guidelines recommend that healthcare professionals address sexuality; however, this is rarely done in practice, due to multiple causes, for example ignorance, embarrassment and lack of systematic treatment. Insight into women's sexual challenges after having a myocardial infarction is much needed. Design: Qualitative interview study. Methods: Qualitative interviews were conducted with 11 patients representative of the population and later transcribed. The analysis was inspired by Ricoeur's theory of interpretation, which consists of three levels: naive reading, structured analysis, and critical interpretation and discussion. Results: The overall finding that emerged regarding the women's sexual health was an anxious resuming of sexual activity. Four themes emerged: (1) the partner, (2) support, (3) the heart disease's influence on sex and (4) the relationship. Conclusion: The women experienced anxious resuming of sexual activity. The heart disease had influence on their sex life, and relationship with their partner could be affected. Some needed support from health professionals or their network to dare sexual activity again. Relevance to clinical practice: This study indicates that health professionals should focus more on identifying anxiety and exhaustion after myocardial infarction and articulating their potential influence on women's sexual lives. Whether this should be addressed in the hospital setting, in the phase 2 rehabilitation at the general practitioner level or in combination has to be considered and may be the basis for further research.